Analisis Pengelolaan Sistem Informasi Manajemen Menggunakan Aplikasi SLIMS 8 Dalam Efesiensi Dan Efektivitas Pelayanan Di UPT Perpustakaan Universitas Dharmawangsa Medan - Yusmiati, Yusmiati; Rangkuti, Sahnan; Firah, Al (Bisnis-Net, 2025)
This research aims to analyze the implementation of management information systems using the SLiMS 8 application in improving the quality of services to users, identifying the obstacles faced and solutions that can be applied to improve the efficiency and effectiveness of services at the Dharmawangsa University Library UPT. Data collection methods involve observation, interviews, and documentation with qualitative descriptive data analysis. The research results show that this application has a big positive impact on visitors, including a faster and more accurate book search process, ease of accessing book collections and other materials, as well as more practical borrowing management, contributing to supporting academic activities. The SLiMS 8 application provides effective digital solutions and supports progress in the world of libraries and education. This application is increasingly developing and has an influence on library performance, encouraging librarians to think creatively and innovatively in information services so that readers' interest in reading increases and the number of library materials increase